The Role of AI-Driven Learning in the Comprehensive Development of Higher Education Professionals: An Empirical Analysis - Vasudevan, Asokan; Singh, Chandra Bhooshan; Jain, Satvik (Journal of Engineering Education Transformations, 2026)
Although Artificial Intelligence (AI) is not a new concept in the field, it is becoming a more significant influence on the educational industry, particularly in the area of training specialized professionals in higher education. This kind of AI- based tools is assisting the teachers to come up with new teaching methods where teaching experiences are tailored to the individual and there is instant feedback. Through these tools, teachers are able to modify their practices to suit many types of learners besides helping themselves to grow professionally. Daily practices, such as grading and administration, can be automated and moved aside, leaving educators with additional time to interact with students and enhance instruction. The paper provides an argument that in spite of the challenges posed by AI, its potential to enhance professional growth and transform the education industry is worth incorporating it in higher education. We consider the potential opportunities and challenges AI gives to higher education and comment on its possibilities to improve comprehensive education of teachers. Once AI is optimized (with a closer understanding), the institutions can remain on the top in the strongly competitive world and educators will provide good education. This quantitative study that was done based on responses of 219 higher education practitioners and teachers. Among the major aspects that have been found in the role of AI-driven learning to holistic development, it is necessary to mention personalized learning experiences, data-driven insights, predictive analytics to make informed decisions, and collaborative learning platforms.